Isolation of Some Microorganisms from Bar Soaps and Liquid Soaps in Hospital Environments - M.H. Zeiny, Sarmad (Iraqi Journal of Pharmaceutical Sciences, 2017)
This study was designed to determine the colonization of the in-use hand washing soaps in hospital settings. It is a comparative cross-sectional research in a surgical specialties and Baghdad teaching hospital in Baghdad, Iraq. Swabs from surfaces of bar soaps and from liquid soaps via their applicator tips; at the sinks of toilets of hospital staff and working rooms of the wards were taken in January 2008. Conventional microbiologic methods were used for culture of the swabs and identification of the isolates. Colonization was detected 60% and 15.9% in bars and liquid forms respectively. And this lead to the conclusion that bar soaps could be colonized with microorganisms excessively. Liquid hand washing soaps are more appropriate in hospital environments. Proper using conditions of the hand washing items should be defined in health care settings.Keywords: Bar soap, liquid soap, pseudomonas aeruginosa, nosocomial infections.